Penyuluhan Bimbingan Remaja Usia Sekolah Dalam Upaya Mencegah Stunting SMKN 1 Jatisari Kecamatan Jatisari Kabupaten Karawang - Rahmawati, Emma Rahmawati; Abdul Malik; Enan Kusnandar; Akke Azhar Anisa (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
Growth is a nutritional issue that impacts the physical growth and development of consciousness of children, especially adolescents in schools who need optimal nutrition to support growth and support learning. Efforts to prevent developmental retardation not only focus on improving children's nutrition to thrive, but it is also very important for adolescents who are future parents who will play a role in breaking the development chain. This service research aims to analyze the effectiveness of school-age adolescent orientation programs in increasing knowledge and awareness of balanced nutrition as an effort to prevent growth retardation. The method used is a qualitative approach and direct counseling at SMKN 1 Jatisari. In this counseling event for guidance for adolescents of young age and prevent stunting, children received advice and nutrition education thanks to media in education and interactive discussions. The results show a new understanding and knowledge in adolescents' knowledge and attitudes towards the importance of balanced nutrition after receiving advice. These observations suggest that adolescent advice at school age is effective in forming an early awareness of the importance of nutrition to avoid developing retardation in the next generation. Therefore, nutrition orientation programs for adolescents must be developed in a sustainable manner thanks to the cooperation between schools, health workers and local KUA as well as STAI students dr. KH. EZ Muttaqien to create a healthy and effective generation.